Orthodontic Patients’ Knowledge and Understanding of Orthodontic Retainers: A cross sectional study - Fenesha, Fatma; Elhabony, Sara (Libyan Journal of Dentistry, 2022)
Objectives: To assess the dental patients’ knowledge and understanding of orthodontic retainers, and to evaluate the level of knowledge in relation to different predefined variables such as gender, onset of treatment and education level. Materials and Methods: This is a cross sectional questionnaire-based study involving patients undergoing active orthodontic treatment. A validated and piloted questionnaire was distributed around five orthodontic clinics in Benghazi city. The paper questionnaire consisted of four sections with 20 questions covering basic demographic data, the knowledge and understanding of orthodontic retainers, and finally the mode of information provision. Descriptive statistics were carried out for frequency and proportions. In addition, the relationship between the variables was analysed using Chi-Square and Fisher exact test. A simple thematic analysis was conducted for the open-ended questions. Results: The response rate was 95%. A total of 295 questionnaires were self-completed and collected from the five centres. The age range was between 16 - 53 years (mean age 24.3). Around 83.4% of patients were aware that they will require a set of orthodontic retainers at the end of treatment. However, only half of the patients knew what type of retainers they will require (56.9%). Regarding the understanding of retention and relapse, around 71.2% of patients understood why retainers are needed and 60% recognize what will happen if they didn't wear their retainers. However, only 34% of the respondents understand what ‘’orthodontic relapse’’ means. No association was found between the onset of treatment, age and gender and the patients’ level of knowledge and understanding of orthodontic retainers. Nevertheless, the level of education was the only variable shown to be associated with the level of patients’ understanding. Conclusions: The level of knowledge and understanding regarding orthodontic retainers was suboptimal among Libyan orthodontic patients. The reported lack of knowledge could potentially influence the amount of compliance with wearing orthodontic retainers. Postgraduate students and professionals seem to be more attentive to instructions and maintaining their teeth in place.